The Active Components of Sunflower (Helianthus annuus L.) Calathide and the Effects on Urate Nephropathy Based on COX-2/PGE2 Signaling Pathway and the Urate Transporter URAT1, ABCG2, and GLUT9 - Dai, Huining; Lv, Shuai; Qiao, Zi'an; Wang, Kaiyu; Zhou, Xipeng; Bao, Chunyang; Zhang, Shitao; Fu, Xueqi; Li, Wannan (Frontiers in Nutrition, 2022)
The sunflower (Helianthus annuus L.) calathide is lately used as an alternative treatment of hyperuricemia; nevertheless, evidence regarding its main components and therapeutic potential in urate nephropathy is lacking. Identification of sunflower calathide aqueous extract (SCE) were subsequently analyzed by UPLC-Q-Orbitrap MS and 32 water-soluble compounds with a comprehensive score greater than 80 were selected. Besides, yeast extract was administrated to induce high levels of UA and hyperuricemic renal injury. We found that SCE treatment not only decreased UA levels to a comparable degree as allopurinol and benzbromarone, but also reduced the BUN levels and participated in kidney injury repair induced by uric acid. Moreover, regulated the expression of URAT1, ABCG2 and inhibit the GLUT9 transporters in normal kidney. Results were multifacetedly evaluated with a view to suggest a possible mechanism of action as compared with those of allopurinol and benzbromarone by western blotting, H&E staining and immunohistochemical. However, the H&E staining suggested histological changes and the uric acid was identified as a cause of renal damage. The anti-inflammatory effect on LPS-induced RAW264.7 cells and the inhibition of COX-2/PGE2 signaling pathway were revealed. Hence, the SCE was not only increased cellular proliferation but downregulated the COX-2/PGE2, NO and IFN-γ cytokines levels in RAW264.7 cells. Conclude, the SCE act on urate transporters and contributed to the prevention of urate nephropathy via cell proliferation and inflammatory process involved in COX-2/PGE2 signaling pathway. It is available to be a food supplement for the application of nephritic inflammation.